A MODEL OF EDUCATION FOR WOMEN (A Case Study in Madrasah Muallimat PUI Majalengka – West Java) - Eti Nurhayati (Jurnal Cakrawala Pendidikan, 2016)
Abstract: This study was aimed to describe a model of education for women in Madrasah Muallimat PUI which had unique and specific characteristics, and it is still maintained until now. It is a special education for Muslimah, aiming to make cadres of educators who are regarded as a noble profession for women. The study used a qualitative approach and the data were collected through literature, documentation, in-depth interviews, and participant observation. The findings showed that: (1) The education in PUI’s perspective: viewing the importance of education for all human beings, integrating the science and religion, education skills, entrepreneurship, faith, noble morality, and innovative skills; (2) The model of education for women in Madrasah Muallimat included: looking at the importance of educated women, learning science and religion, being fluent in reading the Quran, mastering the Arabic language, being able to read the Kitab as a source of religious instruction, having personality as a true Muslimah who is skilled at the field of women to settle down provision, being eloquent, being able to lead the community, being spirited educators and becoming educators for families and communities, as well as being noble. Keywords: Education for women, Madrasah Muallimat, PUI MODEL PENDIDIKAN UNTUK PEREMPUAN (Studi Kasus di Madrasah Muallimat PUI Majalengka - Jawa Barat) Abstrak: Studi ini ingin mendeskripsikan model pendidikan di Madrasah Muallimat PUI yang memiliki karakteristik unik dan spesifik, dan masih dipertahankan sampai sekarang, merupakan pendidikan khusus untuk muslimah, bertujuan mencetak kader pendidik yang dipandang sebagai sebuah profesi mulia untuk perempuan. Studi ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data: studi pustaka, dokumentasi, wawancara mendalam, dan observasi partisipasi. Hasil penelitian ini menyimpulkan: (1) Pendidikan dalam perspektif PUI: memandang pentingnya pendidikan bagi semua manusia, mengintegrasikan pengetahuan umum dan agama, pendidikan keterampilan, wirausaha, keimanan, akhlaq mulia, dan inovatif; (2) Model pendidikan di Madrasah Muallimat adalah: memandang pentingnya perempuan berpendidikan, mempelajari ilmu pengetahuan umum dan agama, fasih membaca al-Qur’an, menguasai bahasa Arab, mampu membaca kitab berbahasa Arab, berkepribadian muslimah yang terampil, pandai berpidato, mampu memimpin masyarakat, berjiwa pendidik dan menjadi pendidik bagi keluarga dan masyarakat, serta berakhlaq mulia. Kata Kunci: Pendidikan untuk perempuan, Madrasah Muallimat, PUI